Fase Resistensi Komunitas Bandung Pyrate Punk Terhadap Industri Musik Populer di Bandung - Yanri Fajar Aghisna Nurcahyana (Pascasarjana ISBI Bandung, 2019)
Punk is a subculture born from the resistance movement. The popular music industry is one of the things opposed by the punk community. In Bandung, music punk was threatened by the dominance of the popular music industry. The entry of industrial elites into the realm of the underground community in Bandung triggered resistance movements from the Bandung Pyrate Punk community. The research methodology used is qualitative using resistance theory from James C. Scott. The focus of the analysis in this study is the phases of resistance from Bandung Punk Pyrate community. The results of this study indicate that resistance from Bandung Pyrate Punk goes through several phases, namely the movement phase, building awareness, influencing target groups and achievements. They fight by marginalizing themselves to avoid the flow of the popular music industry. This leads to creative ideas about producing, marketing, and also creating artworks. These processes are an effort to maintain the continuity of the musical activities of the punk community.Keywords: Punk, Resistance, Music, Industry, Popule